Social Media Management In Islamic Content Production: Study On Instagram @Sobat Islami - Sopiyan, Wawan; Sihabudin, Dede; Rochmansyah, Erwin; Solimin, Solimin (El-Ghiroh : Jurnal Studi Keislaman, 2025)
This study aims to analyze the social media management strategy of the Instagram account @Sobat Islami in producing Islamic content, with a focus on the effectiveness of delivering religious messages in the digital era. Social media, especially platforms such as Instagram, has become a potential tool in disseminating Islamic values ??to a wider audience. This study explores various aspects of management, including content planning, scheduling, managing interactions with followers, and utilizing creative features such as videos and images. The results show that an effective social media management strategy plays an important role in increasing the appeal and spread of Islamic content. With a structured approach, social media accounts are able to convey messages that are relevant, inspiring, and in accordance with Islamic values, while strengthening relationships with digital communities. This study contributes to the understanding of the use of social media as an innovative modern means of da'wah.